MATURASI LELE MUTIARA Clarias gariepinus BETINA MELALUI PENAMBAHAN HORMON OODEV DAN ESTRADIOL-17ß PADA PAKAN - Oktavia Rugus Ayu Enditha; Deny Sapto Chondro Utomo; Munti Sarida (Universitas Sriwijaya, 2021)
The problem in Mutiara strain of North African catfish Clarias gariepinus culture is that the production of both larvae and seeds is still inhibited by the seasonal reproductive cycle where the catfish only spawn once during the spawning season. The purposes of this study were to evaluate the effect of administration of oodev and estradiol-17ß on the maturity process and to determine the best doses in accelerating the maturion of female Mutiara strain. This study used a Completely Randomized Design with 5 treatments and 3 individual replications. The treatments were combination between dose Oodev (PMSG and Anti-Dopamine) and dose Estradiol-17ß in feed (both doses in ml/kg feed):A(0+0), B(0.5+0), C(0+0.6), D(0.5+0,6), E(1+1). The results of this study showed that the administration of Oodev and Estradiol-17ß significant affect on gonadal maturity index about 82.21% compared to control and acclerating maturation of female mutiara strain with doses the best is the treatment E (oodev 1 ml/kg feed+estradiol-17ß 1 ml/kg feed).Key words: Clarias gariepinus, dose, estradiol-17ß, maturation, oodev